2018
DOI: 10.1029/2018gl077393
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tectonic Stress in Triggering Large Silicic Caldera Eruptions

Abstract: We utilize 3-D temperature-dependent viscoelastic finite element models to investigate the mechanical response of the host rock supporting large caldera-size magma reservoirs (volumes >10 2 km 3 ) to local tectonic stresses. The mechanical stability of the host rock is used to determine the maximum predicted repose intervals and magma flux rates that systems may experience before successive eruption is triggered. Numerical results indicate that regional extension decreases the stability of the roof rock overly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 33 publications
0
19
1
Order By: Relevance
“…This can be carried out with models specific to volcanic systems containing heterogeneous crustal properties, provided by seismic tomography, spatially variable rheological effects through the use of viscoelastic shells within an elastic medium (e.g., Currenti, ; Currenti & Williams, ; Delgado et al, ; Newman et al, ; Segall, ), or a temperature‐dependent viscosity distribution that accounts for crustal geotherms and the perturbation owing to a modeled magmatic source (Del Negro et al, ; Gottsmann et al, ; Gottsmann & Odbert, ; Gregg et al, ; Hickey et al, ). Further to this, an important consideration is the influence of regional stresses and strain fields (Costa et al, ; Currenti & Williams, ), such as active extension within the Taupo Volcanic Zone (e.g., Cabaniss et al, ), on the observed viscoelastic behaviors and the resultant deformation time series.…”
Section: Discussionmentioning
confidence: 99%
“…This can be carried out with models specific to volcanic systems containing heterogeneous crustal properties, provided by seismic tomography, spatially variable rheological effects through the use of viscoelastic shells within an elastic medium (e.g., Currenti, ; Currenti & Williams, ; Delgado et al, ; Newman et al, ; Segall, ), or a temperature‐dependent viscosity distribution that accounts for crustal geotherms and the perturbation owing to a modeled magmatic source (Del Negro et al, ; Gottsmann et al, ; Gottsmann & Odbert, ; Gregg et al, ; Hickey et al, ). Further to this, an important consideration is the influence of regional stresses and strain fields (Costa et al, ; Currenti & Williams, ), such as active extension within the Taupo Volcanic Zone (e.g., Cabaniss et al, ), on the observed viscoelastic behaviors and the resultant deformation time series.…”
Section: Discussionmentioning
confidence: 99%
“…We utilize this twenty-two-year record of deformation to constrain 3D finite element models which hindcast the 2011 and 2015 eruptions of Axial Seamount. In particular, we expand upon the approach of Cabaniss et al 18 and use the COMSOL Multiphysics 5.4 modeling software to calculate stress and strain in the modeled host rock surrounding the expanding Axial magma reservoir, which is modeled as a pressurized void filled with an idealized fluid. The geometry of the simulated reservoir is approximated from a previously identified region of high melt fraction within the body of the main magma reservoir (MMR) at Axial Seamount 28,29 .…”
Section: Modeling Historical Eruptions Of Axial Seamountmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ void space from which volumetric change and flux rate required to reproduce the observed deformation at the seafloor are estimated. As in Cabaniss et al 18 , Mohr-Coulomb and tensile failure are calculated throughout the model space along with Andersonian stress orientations 30 to determine fault type and orientation in regions where failure is calculated. For this study, eruption is defined as the first occurrence of tensile failure at the magma reservoir boundary coincident with through-going Mohr-Coulomb failure (effectively linking the reservoir to the surface).…”
Section: Modeling Historical Eruptions Of Axial Seamountmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the relationship between failure and eruptions is unclear. Throughgoing failure which connects the magma chamber to the surface has been indicated as a potential catalyst of caldera formation eruptions (e.g., Cabaniss et al, ; Gregg et al, , ). However, large caldera eruption cycles may be much longer than thousands of years, far outside of the time scales in this investigation.…”
Section: Discussionmentioning
confidence: 99%